Photochemical Synthesis of cis, trans, cis‐1, 2, 3, 4‐Tetrakis(diphenylphosphanyl)buta‐1, 3‐diene and Its Metal Coordination. Issue 46 (30th November 2018) - Prock, Johannes; Ehrmann, Katharina; Viertl, Wolfgang; Pehn, Richard; Pann, Johann; Roithmeyer, Helena; Bendig, Marvin; Rodríguez Villalón, Alba; Kopacka, Holger; Dumfort, Alexander; Oberhauser, Werner; Clausing, Simon T.; et al.
Abstract: Invited for the cover of this issue is the group of Peter Brüggeller from the University of Innsbruck, Austria. The cover image shows the multi‐step synthesis of dppbd. Abstract : One can see in this publication that we give way to our curiosity of how chemistry works in its deepest roots … Read more about the story behind the cover in the Cover Profile and about the research itself in theFull Paper by W. Oberhauser, G. Knör, P. Brüggeller et al.